Ethics and the COVID-19 pandemic; A clinician’s perspective - Kulkarni, Rajesh K; Kinikar, Aarti A (Journal of Nepal Paediatric Society, 2020)
The COVID-19 pandemic has raised exigent medical, ethical and organizational challenges. While some excellent articles have been published about the ethical aspects of pandemics from a bioethicist’s perspective , there is meager published literature on clinician’s perspective. The issues important from a clinician’s point of view are duty to treat, personal safety, safety of family, safety of colleagues, resource allocation, care for non COVID-19 patients and research.